Toxicity effects of the organic UV-filter 4-Methylbenzylidene camphor in zebrafish embryos. (March 2019) - Quintaneiro, Carla; Teixeira, Bruna; Benedé, Juan L.; Chisvert, Alberto; Soares, Amadeu M.V.M.; Monteiro, Marta S.
Abstract: Ultraviolet (UV) filters are widely used in personal care products and due to their lipophilicity these chemicals tend to bioaccumulate in the aquatic biota. 4-Methylbenzylidene camphor (4-MBC) is one of the most used UV-filters, and it is commonly detected in freshwater fish tissues. This substance is suspected to be an endocrine disruptor due to its interaction with Hypothalamus-Pituitary-Gonadal (HPG) and HP-Thyroid (HPT)-axis. The main objective of this study was to evaluate the effects of 4-MBC on apical endpoints, biochemical markers and on genes involved in endocrine pathways in Danio rerio . Zebrafish embryos were exposed to 4-MBC (0.083–0.77 mg/l) from 0 to 96 h post-fertilization (hpf). Hatching, heart rate and malformations were the apical endpoints assessed. Alterations on neurotransmission and oxidative stress were evaluated through acetylcholinesterase (AChE), catalase (CAT) and glutathione S-transferase (GST) enzymatic activities. Endocrine effects were analysed by the expression of genes involved in HPG and HPT-axis of embryos exposed 96 h to the EC10 of 4-MBC (0.19 mg/l). Exposure to 4-MBC induced morphological abnormalities during embryonic development, including notochord curvature, delayed absorption of yolk sac and pericardial oedema. Concentration of 0.77 mg/l 4-MBC decreased embryo heart rate at 48h. At neurotransmission level, an induction of AChE at concentrations above 0.15 mg/l was observed. Malformations and decreased heart rate along with alterations observed at neurotransmission level might have compromised zebrafish larvae equilibrium. Glutathione S-transferase induction above 0.15 mg/l 4-MBC suggests activation of detoxification processes. Furthermore, observed brain aromatase gene down-regulation by 4-MBC suggests impairment of normal functioning of HPG axis in zebrafish. Graphical abstract: Image 1 Highlights: 4-MBC decreased heart rate and caused pericardial oedemas in zebrafish embryos. 4-MBC activated a detoxification process and impaired neurotransmission. Exposure to 4-MBC down-regulated brain aromatase gene.